Prevalence and Determinants of Overweight, Obesity, and Type 2 Diabetes Mellitus in Adults in Malaysia. (March 2015) - Jan Mohamed, Hamid Jan B.; Yap, Roseline Wai Kuan; Loy, See Ling; Norris, Shane A.; Biesma, Regien; Aagaard-Hansen, Jens
This systematic review aimed to examine trends in overweight, obesity, and type 2 diabetes mellitus (T2DM) among Malaysian adults, and to identify its underlying determinants. A review of studies published between 2000 and 2012 on overweight, obesity, and T2DM was conducted. The Cochrane library of systematic reviews, MEDLINE, EMBASE, Biosis, Scopus, and MyJurnal digital database were searched. According to national studies, the prevalence of overweight increased from 26.7% in 2003 to 29.4% in 2011; obesity prevalence increased from 12.2% in 2003 to 15.1% in 2011, and T2DM prevalence was reported as 11.6% in 2006 and 15.2% in 2011. Distal determinants of increased risk of overweight, obesity, and T2DM were as follows: female, Malay/Indian ethnicity, and low educational level. The limited number of studies on proximal determinants of these noncommunicable diseases (NCDs) indicated that an unhealthy diet was associated with increased risk, whereas smoking was associated with decreased risk. However, more studies on the proximal determinants of overweight, obesity, and T2DM within the Malaysian context are needed. Overall, our findings provide insights for designing both future investigative studies and strategies to control and prevent these NCDs in Malaysia.